2005
DOI: 10.1177/0018726705052183
|View full text |Cite
|
Sign up to set email alerts
|

Subtextual gendering processes: A study of Japanese retail firms in Hong Kong

Abstract: This study examined equal opportunities for women employees in two Japanese-owned retail companies (Tairo and Okadaya) in Hong Kong. This article initially discusses the various explanations for gender inequality put forward by scholars. Since equal opportunities legislation – specifically the Sex Discrimination Ordinance (SDO) – was introduced in Hong Kong in 1996, little research has been able to explain why gender inequality persists. The issue can alternatively be understood by examining the subtextual gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(18 reference statements)
3
11
0
Order By: Relevance
“…While Max's gender equality drive saw only ‘three junior managers and two middle managers’ at the head office, arguably the organizational location where the most significant decision‐making powers are concentrated, the review above of RetailJapan's appointments, particularly after the inclusion initiatives, suggest that the opportunities provided by this large multinational for women to pursue managerial careers were both proportionally higher than is typical in retailing, and, while still small, nevertheless considerable in terms of sheer numbers as well. In fact, the difference between Max and RetailJapan also involves a difference in the definition of managerial roles, the former counting primarily supervisory roles characterized by relatively routine management tasks, and the latter mostly involving ranks of greater decision‐making power, expertise and flexibility (Wong, 2005, p. 269).…”
Section: The Case Of Retailjapan — Research Setting and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…While Max's gender equality drive saw only ‘three junior managers and two middle managers’ at the head office, arguably the organizational location where the most significant decision‐making powers are concentrated, the review above of RetailJapan's appointments, particularly after the inclusion initiatives, suggest that the opportunities provided by this large multinational for women to pursue managerial careers were both proportionally higher than is typical in retailing, and, while still small, nevertheless considerable in terms of sheer numbers as well. In fact, the difference between Max and RetailJapan also involves a difference in the definition of managerial roles, the former counting primarily supervisory roles characterized by relatively routine management tasks, and the latter mostly involving ranks of greater decision‐making power, expertise and flexibility (Wong, 2005, p. 269).…”
Section: The Case Of Retailjapan — Research Setting and Methodologymentioning
confidence: 99%
“…It is worth noting that the disadvantaged position of women in fact constitutes a central theme in most early and contemporary writing on Japanese multinational corporations abroad (Ong, 1987; Saso, 1990; Taylor, 2006; Wong, 2005). It is therefore not surprising that recent research finds that many qualified women in Japan do not share the general reluctance, especially outside the core metropolitan areas, of Japanese graduates to work for foreign employers and in fact would like to work for them (Lundberg, 2006, p. 11).…”
Section: Women's Employment and Foreign Employers In The Japanese Conmentioning
confidence: 99%
“…For example, Martin (1980: 186) found that policewomen must choose between either 'defeminization (and its emphasis on occupational role obligations) and deprofessionalization (and emphasis on meeting sex role norms while on the job)'. Similarly, Wong (2005) found that women in senior management positions identified themselves with masculinity and suppressed feminine identities in order to demonstrate competence and capability. As Levin (2001) explains in a study of stock traders, 'the contradiction lies in the fact that for a woman to be one of guys [sic], she has to stop being feminine' (p. 125).…”
Section: Gender and Identity In Male-dominated Occupationsmentioning
confidence: 99%
“…Metaphors contribute to premise reflection by challenging the identification-or the definition-of the problem by finding a new representation that can reorient this problem-solving task (Mezirow, 1990). Alternatively, instructors can compare and contrast the cultural perspective, which is widely used in international business education, with other perspectives on gender equality, such as power or gender subtext (see discussion of seven perspectives in Wong, 2005). Another option could result in considering the discussion of gender mainstreaming and the many efforts invested by a multitude of stakeholders to increase gender equality in business settings across the world (e.g., Thompson, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Another worthwhile option is to introduce the topic of gender equality conceptually. By discussing the many perspectives on gender equality (e.g., Kemp, 2016; Maier, 1997; Thompson, 2008; Wong, 2005), international business education instructors can encourage reflection on the very premises guiding students beliefs, attitudes, and behaviors around gender equality. For example, instructors could pick two contrasting perspectives and analyze how business leaders, both females and males, respond to gender (in)equality issues at work.…”
Section: Next Stepsmentioning
confidence: 99%